Application of steam explosion treatment on the collagen peptides extraction from cattle bone. (May 2023) - Zhang, Hongru; Liu, Hong; Qi, Liwei; Xv, Xiong; Li, Xia; Guo, Yujie; Jia, Wei; Zhang, Chunhui; Richel, Aurore
Abstract: In this study, steam explosion (SE) treatment was applied to extract collagen peptides from cattle bone. The SE treatment conditions included steam pressure: 1.5 MPa (200.43 °C), 2.0 MPa (213.85 °C), and 2.5 MPa (224.99 °C), and reaction time: 10 min, 20 min, and 30 min. With the increase of pressure and reaction time, the protein recovery rate improved, and reached to 60.5% at 2.0 MPa–30 min. SE significantly decreased the molecular weight of collagen peptides ( P  < 0.05) with increasing pressure and reaction time. However, at 2.5 MPa, SE darkened the sample color resulting in dark yellow. Particle size analysis and SEM images indicated that SE decreased the particle size and destroyed microstructure of cattle bone powder. FT-IR analysis showed that SE induced distinct characteristic peaks of hydroxyapatite in cattle bone powder. SE facilitated peptides release from collagen by destroying peptide bonds and enzymatic cross-links. Amino acid analysis indicated SE could not change the amino acid composition of collagen peptides. The calcium-binding ability and osteoblast proliferative activity of extracted collagen peptides were 44.7 μg/mg and 126.7% (200 μg/mL), respectively. The findings put forward data support and a scientific basis for the application and development of SE technology to collagen peptides extraction and high-value utilization of cattle bone. Highlights: Collagen peptides were extracted from cattle bone by steam explosion treatment. The protein recovery rate reached 60.5% under 2.0 MPa-30 min. SE significantly decreased the molecular weight distribution of peptides. SE destroyed the physical and chemical structures of cattle bone.